2019
DOI: 10.3847/1538-4357/ab426f
|View full text |Cite
|
Sign up to set email alerts
|

Using X-Ray Morphological Parameters to Strengthen Galaxy Cluster Mass Estimates via Machine Learning

Abstract: We present a machine-learning approach for estimating galaxy cluster masses, trained using both Chandra and eROSITA mock X-ray observations of 2041 clusters from the Magneticum simulations. We train a random forest (RF) regressor, an ensemble learning method based on decision tree regression, to predict cluster masses using an input feature set. The feature set uses core-excised X-ray luminosity and a variety of morphological parameters, including surface brightness concentration, smoothness, asymmetry, power … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 94 publications
(112 reference statements)
0
35
0
Order By: Relevance
“…For example, with a luminosity thresholded sample of 41 nearby clusters, Mulroy et al (2019) have shown that there is a strong correlation between the central gas entropy and residual of cluster observables about the mean relation. Morphological properties of the hot gas can also be employed to construct a more complex mass-observable relation to reduce the scatter (Green et al 2019). An interesting direction would be to check if the X-ray morphological parameters are a better indicator of the age or can more efficiently reduce the scatter.…”
Section: Hot Gas Observables As Secondary Explanatory Variablementioning
confidence: 99%
“…For example, with a luminosity thresholded sample of 41 nearby clusters, Mulroy et al (2019) have shown that there is a strong correlation between the central gas entropy and residual of cluster observables about the mean relation. Morphological properties of the hot gas can also be employed to construct a more complex mass-observable relation to reduce the scatter (Green et al 2019). An interesting direction would be to check if the X-ray morphological parameters are a better indicator of the age or can more efficiently reduce the scatter.…”
Section: Hot Gas Observables As Secondary Explanatory Variablementioning
confidence: 99%
“…To be mentioned also other approaches based on wavelets analysis (Pierre & Starck 1998), on the Minkowski functionals (Beisbart et al 2001), or on machine learning (see e.g. Cohn & Battaglia 2019;Green et al 2019;Gupta & Reichardt 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For galaxy cluster studies only, ML algorithms have been extensively used to successfully compute their properties such as their masses (e.g., Ntampaka et al 2015Ntampaka et al , 2016 Article number, page 1 of 11 arXiv:1911.10778v1 [astro-ph.CO] 25 Nov 2019 A&A proofs: manuscript no. aanda Green et al 2019;Calderon & Berlind 2019;Ho et al 2019). Therefore, those very powerful algorithms may help us in the near future to deal with the huge amount of data the community is collecting, and to answer some open questions in astrophysics and cosmology.…”
Section: Introductionmentioning
confidence: 99%